Do executives benefit from shareholder disputes? Evidence from multiple large shareholders in Chinese listed firms - Fang, Yuanli; Hu, Maggie; Yang, Qingsen (Journal of Corporate Finance, 2018)
Prior research documents that ownership by multiple large shareholders (MLS) could alleviate agency conflicts between controlling shareholders and small shareholders through improved monitoring. We provide evidence of a “dark side” to MLS. Using a sample of Chinese listed firms during 2005–2014, we find a positive association between the presence of MLS and excess executive compensation. Furthermore, excess compensation is greater in firms in which the different types of large shareholders have relatively equal voting power. Overall, these results imply that coordination friction among MLS reduces large shareholders' monitoring efficiency and exacerbates agency problems between shareholders and executives.